Contextual Pop Up Book as an Innovative Learning Media in Social Science Subjects in Elementary Schools - Halimah, Halimah; Putri , Dina Eka; Wulandari, Wulandari; Adewumi, Sunday Eric; Arce-Calderón, Xiomara (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This research aims to produce a product in the form of a valid and practical contextual-based Pop Up Book media. Methodology: This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The tool used is Pop Up Book as an interactive visual media for learning. Data collection techniques include observation, interviews, and questionnaires. Validation is carried out by experts with validation sheets, while questionnaires and observations are used to measure the effectiveness and practicality of this learning media. Main Findings: The development of a contextual Pop Up Book for Social Science education in elementary schools showed positive results. The book was validated as highly suitable for the curriculum and effective for engaging students. User testing revealed good student interest and participation, although improvements in engagement and material understanding were needed. The book effectively connects learning with daily life experiences, but some students required more support in retaining and understanding the content. Overall, the Pop Up Book was deemed beneficial but with room for refinement. Novelty/Originality of this study: This research offers innovation in developing contextual-based Pop Up Book media for learning Social Sciences in Elementary Schools. The uniqueness lies in the three-dimensional interactive design that connects the material with students' daily lives, increasing their involvement and understanding. This provides a new contribution to a more interesting and effective learning method